Preparation method of antistatic folding filter cartridge

By using mixtures and conductive fabrics of synthetic fibers and metal fibers in high -temperature flue filtration equipment, and setting metal roll nets and galvanized metal end caps to solve the problem of insufficient anti -static performance of the equipment, achieve more efficient static electrical electrical electricity Protection and filtration effect.

CN119345807AActive Publication Date: 2025-01-24NANJING JIHUA 3521 ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411654829.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-24
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The antistatic performance of existing high-temperature flue gas filtration equipment is insufficient, making it difficult to effectively prevent the risk of fire or explosion caused by static electricity.

Method used

A mixture of synthetic fibers and metal fibers is used as the filter cartridge material, and a metal rolled mesh and a galvanized metal end cover are set inside the filter cartridge. Cloth containing conductive fibers is used as the base cloth. Through mesh laying, meshing, pre-needle punching and Spunlace reinforcement and other processes are used to prepare antistatic pleated filter cartridges.

Benefits of technology

A significant reduction of the volume resistance of the filter tube, improving anti -static performance, and effectively prevent static accumulation and discharge. It is suitable for the high -temperature flue gas filtration environment in the coal mining industry, chemical industry and oil and gas mining industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141876880000091
    Figure BDA0005141876880000091
  • Figure BDA0005141876880000101
    Figure BDA0005141876880000101
Patent Text Reader

Abstract

The invention relates to the technical field of high-temperature flue gas filtration, and particularly discloses a preparation method of an antistatic folding filter cartridge. The method comprises the following steps: opening and mixing synthetic fibers and metal fibers, and carrying out carding, lapping, grid connection and pre-needling by taking cloth containing conductive filaments as base cloth to obtain a pre-needled felt; the pre-needled felt is subjected to spunlace reinforcement, and a filter material plain felt is obtained; singeing the filter material plain felt, soaking the filter material plain felt in a finishing agent, mangling, and drying to obtain a stiff filter material felt material; after the stiff filter material felt material is subjected to edge cutting and folding, a fixing bandage is welded, a center joint of the stiff filter material felt material is welded, and a cylindrical filter material is obtained; installing a metal roll net in the cylindrical filter material, and welding a seal of a fixing bandage to obtain a filter cartridge main body part; and mounting galvanized metal end covers at the two ends of the filter cartridge main body part to obtain the antistatic folding filter cartridge. The antistatic performance of the filter cartridge can be improved, so that the filter cartridge is more suitable for special working environments of the coal mining industry, the chemical industry and the oil and gas exploitation industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature smoke filtration, and in particular to a method for preparing an antistatic folded filter cartridge. Background Art

[0002] Dust removal bags are widely used in the high-temperature flue gas filtration industry. In some special working environments, such as coal mining, chemical industry, and oil and gas mining industry, due to flammable substances such as coal ash powder and flammable gas, if the dust rubs against the surface fiber of the filter material to generate static electricity, it may cause serious accidents such as fire or explosion. Therefore, when using filter bags to filter dust, the filter bags need to have antistatic properties.

[0003] In the related art, Chinese patent CN109435375A discloses a dust removal bag, in which the filter bag is processed into a bag shape by filter material. The filter material includes a first layer and a second layer from top to bottom. The first layer and the second layer can be composed of glass fibers. The glass fibers used for the first layer and the second layer can be the same type or different types of glass fibers, or mixed types of fibers. The mixed type refers to that the diameters of the glass fibers can be different.

[0004] Since glass fiber, PPS, aramid, polyester and other fibers are fiber materials with extremely low conductivity and are prone to accumulate static electricity, the dust removal bags disclosed in the above-mentioned related technologies have poor antistatic properties and it is difficult to avoid the risks of explosion and fire caused by static electricity in special environments. Summary of the invention

[0005] In order to improve the antistatic performance of a filter cartridge, the present application provides a method for preparing an antistatic folded filter cartridge.

[0006] The present application provides a method for preparing an antistatic folded filter cartridge, which adopts the following technical scheme:

[0007] A method for preparing an antistatic folded filter cartridge comprises the following steps:

[0008] The synthetic fiber and the metal fiber are opened separately, and mixed in a weight ratio of 100:(5-10) of the synthetic fiber:the metal fiber to obtain a mixed fiber, and the cloth containing the conductive yarn is used as the base fabric, and the mixed fiber is combed, laid, combined and pre-needled to obtain a pre-needled felt;

[0009] The pre-needled felt is subjected to hydroentanglement reinforcement to obtain a filter material felt;

[0010] After the surface of the filter material felt is singed, it is immersed in a finishing agent, and the impregnated filter material felt is squeezed and dried to obtain a stiff filter material felt;

[0011] After trimming and folding the stiff filter material felt, a fixing band is welded on the outer side of the stiff filter material felt, and the center seam of the stiff filter material felt is welded to obtain a cylindrical filter material;

[0012] A metal mesh roll is installed inside the cylindrical filter material, and the sealing of the fixing band is welded to obtain the main body of the filter cartridge;

[0013] Galvanized metal end caps are installed at both ends of the main part of the filter cartridge to obtain an antistatic pleated filter cartridge.

[0014] By adopting the above technical solution, a mixture of synthetic fiber and metal fiber is used as the raw material, and a cloth containing conductive thread is used as the base cloth. Since the conductivity of metal fiber is higher than that of synthetic fiber, and the base cloth itself is also conductive, the volume resistance of the filter material can be effectively reduced. Moreover, the present application adopts the form of a filter cartridge to replace the traditional filter bag and skeleton separation matching, and a metal mesh is arranged in the filter cartridge, and galvanized metal end caps are arranged at both ends, which can not only increase the filtration area, but also through structural improvements, the metal mesh and the galvanized metal end caps can be matched, which can effectively reduce the charge accumulation of the folded filter cartridge and reduce the overall volume resistance of the folded filter cartridge. Therefore, the present application can improve the antistatic performance of the filter cartridge, making the filter cartridge more suitable for the special working environment of the coal mining industry, chemical industry and oil and gas extraction industry.

[0015] In a specific embodiment, the finishing agent includes the following raw materials in weight percentage: 20-30% stiffening agent, 3-5% antistatic agent, 10-15% PTFE emulsion, 1-3% coupling agent, and the balance is water.

[0016] By adopting the above technical solution and using a finishing agent containing an antistatic agent, during the impregnation process, the antistatic agent can penetrate into the interior and surface of the filter material, further reducing the volume resistance of the filter material, thereby improving the antistatic performance of the filter material itself.

[0017] In a specific embodiment, the antistatic agent includes potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline microspheres in a weight ratio of 1:(0.6-1.2):(0.3-0.6).

[0018] By adopting the above technical scheme, the chemical stability of the potassium salt of fatty alcohol ether phosphate is good, which can prevent the corrosion of metal fibers and cause rust, and can also reduce the friction coefficient between fibers and the surface resistance of fibers, thereby effectively inhibiting the generation of static charge. The sodium salt of octadecylbenzenesulfonic acid helps to improve the surface activity of the potassium salt of fatty alcohol ether phosphate and the conductive polyaniline microspheres, promote the penetration of the potassium salt of fatty alcohol ether phosphate and the conductive polyaniline microspheres into the fibers and inside the base fabric, and the conductive polyaniline microspheres can form a continuous conductive path between the non-woven fibers, significantly reduce the overall volume resistance of the filter material, and improve the overall conductive performance of the filter material, thereby effectively preventing the accumulation of static electricity and the occurrence of discharge phenomena.

[0019] In a specific embodiment, the weight of the stiff filter felt material is 330-370 g / m 2 .

[0020] By adopting the above technical solution, the gram weight of the stiff filter felt material is related to the amount of glue applied. If the amount of glue applied is too large, the stiff filter felt material will be too brittle, which will damage the strength during the subsequent folding operation, resulting in the final antistatic folded filter cartridge being easily worn, pilling or broken. If the amount of glue applied is too low, the stiff filter felt material will be easily deformed, and its fiber structure may change, which will easily affect the adsorption and filtration effects of the antistatic folded filter cartridge. The present application has found through experiments that by controlling the gram weight of the stiff filter felt material within the above range, the antistatic folded filter cartridge obtained has good adsorption and filtration effects, and is not easy to wear, pilling or break.

[0021] In a specific embodiment, the weight of the filter material felt is 285-315 g / m 2 .

[0022] By adopting the above technical solution, the weight of the filter material felt affects the thickness and the amount of glue applied to the stiff filter material felt in the subsequent steps, and the thickness also affects the folding performance of the stiff filter material felt. The present application controls the weight of the filter material felt within the above range in advance, which helps to adjust the weight of the stiff filter material felt to 330-370g / m in the subsequent steps. 2 , making the stiff filter felt material easy to fold, and having good adsorption and filtration effects and good durability.

[0023] In a specific implementation scheme, the impregnated filter material felt is squeezed and dried at a pressure of 7-8 bar. After squeezing, the liquid content of the impregnated filter material felt is 50-70%; the drying temperature is 140℃-240℃.

[0024] By adopting the above technical solution, the present application has found through experiments that by squeezing the liquid under the above pressure, the liquid carrying rate of the impregnated filter material felt can be controlled at 50-70%. At the above liquid carrying rate and drying temperature, it can be quickly dried and a gram weight of 330-370g / m 2 The stiff filter felt material helps to improve the durability and production efficiency of the present application. Moreover, the present application found that the volume resistivity of the antistatic pleated filter cartridge finally obtained by adopting the above process conditions is lower, which shows that the above process conditions also help to improve the finishing effect of the finishing liquid and improve the antistatic performance of the pleated filter cartridge.

[0025] In a specific embodiment, the pre-needling density is 60-100 needles / cm 2 The needle puncture depth is 11-15mm, and the water puncture pressure of water puncture reinforcement is 260-360bar.

[0026] By adopting the above technical solution, since the pre-needling density affects the stiffness of the needle felt, and the needling depth affects the thickness of the pre-needling felt, the higher the water entanglement pressure, the greater the water entanglement energy generated, the entanglement degree of the filter material felt increases, the thickness decreases, and the strength increases. Therefore, the thickness and stiffness can be prepared by reasonably regulating the pre-needling density and needling depth of the pre-needling and the water entanglement pressure of the water entanglement reinforcement. The present application has found through experiments that the filter material prepared by adopting the above-mentioned pre-needling and water entanglement reinforcement process conditions is not only easy to fold, but also has a suitable stiffness, is not easy to wear and fluff, and has good durability.

[0027] In a specific embodiment, the synthetic fiber includes at least one of polyester fiber, aramid fiber or PPS fiber, and the conductive yarn-containing fabric is any one of polyester fabric, aramid fabric or PPS fabric containing conductive yarn in both the warp and weft directions.

[0028] By adopting the above technical solutions, polyester has excellent wrinkle resistance, is not easy to wrinkle, has high strength and elastic recovery ability, is durable and wear-resistant. Aramid has high strength, excellent high temperature resistance, chemical corrosion resistance and self-extinguishing properties. PPS has excellent heat resistance, chemical resistance and flame retardant properties. The fibers and fabrics of these three materials can be used to make the filter cartridge of this application, and the obtained filter cartridge can adapt to the high temperature flue gas filtration environment and has good durability.

[0029] In summary, this application has the following beneficial effects:

[0030] 1. The present application can effectively reduce the charge accumulation of the pleated filter cartridge, reduce the overall volume resistance of the pleated filter cartridge, and improve the antistatic performance of the filter cartridge, making the filter cartridge more suitable for the special working environment of the coal mining industry, chemical industry, and oil and gas extraction industry.

[0031] 2. In the present application, a mixture of potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline is preferably used as an antistatic agent, which can significantly reduce the overall volume resistance of the filter material and improve the overall conductivity of the filter material, thereby effectively preventing the accumulation and discharge of static electricity. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0033] Example

[0034] Example 1

[0035] This embodiment provides a method for preparing an antistatic folded filter cartridge, which comprises the following steps:

[0036] The polyester fiber and the stainless steel fiber were opened separately, and mixed in a weight ratio of 100:8 to obtain a mixed fiber. The polyester fabric containing conductive yarns in both the warp and weft directions was used as the base fabric. After the mixed fiber was combed, it was laid, combined and pre-needled. The needle-punching density was 80 needles / cm 2 The needle punching depth is 13 mm to obtain a pre-needled felt.

[0037] The pre-needled felt was hydroentangled with 5 hydroentanglement heads, a hydroentanglement pressure of 310 bar, and a vehicle speed of 5.5 m / min to obtain a filter material felt.

[0038] The surface of the filter material felt is singed at a singeing speed of 26 m / min. After singeing, it is immersed in a finishing agent, and the impregnated filter material felt is squeezed with liquid at a pressure of 7.5 bar. After squeezing, the impregnated filter material felt has a liquid rate of 62%. Then it is dried and shaped in an oven at a drying temperature of 190°C and an oven speed of 5 m / min to obtain a stiff filter material felt. Among them, the finishing agent includes the following raw materials in weight percentage: 25% stiffening agent (Xinyi Synthesis LB814), 4% antistatic agent, 10% PTFE emulsion (AMP-95), 1% KH550 coupling agent, and the balance is water. The antistatic agent is a mixture of fatty alcohol ether phosphate potassium salt (MOA-3PK), octadecylbenzene sulfonic acid sodium salt and conductive polyaniline microspheres (Xinyuhong xyh001) in a weight ratio of 1:1:0.5.

[0039] After trimming the stiff filter felt material, it is sent to a folding machine for folding with a folding depth of 25 mm. A fixing strap made of the same material as the stiff filter felt material is welded to the outer side of the stiff filter felt material, and an ultrasonic welding machine is used to weld the center seam of the stiff filter felt material to obtain a cylindrical filter material.

[0040] A stainless steel mesh roll is installed inside the cylindrical filter material, and the sealing of the fixing band is welded by a welding machine to obtain the main body of the filter cartridge.

[0041] The two ends of the main body of the filter cartridge are placed in galvanized metal end caps matching the size of the filter cartridge, and fixed by glue to obtain an antistatic folded filter cartridge.

[0042] Example 2

[0043] The only difference between this embodiment and embodiment 1 is that the polyester fiber and the stainless steel fiber are mixed in a weight ratio of 100:5 to obtain the mixed fiber.

[0044] Example 3

[0045] The only difference between this embodiment and embodiment 1 is that the polyester fiber and the stainless steel fiber are mixed in a weight ratio of 100:10 to obtain the mixed fiber.

[0046] Example 4

[0047] The difference between this embodiment and embodiment 1 is that the finishing agent includes the following raw materials in weight percentage: 20% stiffening agent, 3% antistatic agent, 15% PTFE emulsion, 3% KH550 coupling agent, and the balance is water.

[0048] Example 5

[0049] The only difference between this embodiment and embodiment 1 is that the finishing agent includes the following raw materials in weight percentage: 30% stiffening agent, 5% antistatic agent, 13% PTFE emulsion, 2% KH550 coupling agent, and the balance is water.

[0050] Example 6

[0051] The only difference between this embodiment and embodiment 1 is that the antistatic agent is a mixture of potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline microspheres in a weight ratio of 1:0.5:0.2.

[0052] Example 7

[0053] The only difference between this embodiment and embodiment 1 is that the antistatic agent is a mixture of potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline microspheres in a weight ratio of 1:0.6:0.3.

[0054] Example 8

[0055] The only difference between this embodiment and embodiment 1 is that the antistatic agent is a mixture of potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline microspheres in a weight ratio of 1:1.2:0.6.

[0056] Example 9

[0057] The only difference between this embodiment and embodiment 1 is that the antistatic agent is a mixture of potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonate and conductive polyaniline microspheres in a weight ratio of 1:1.4:0.7.

[0058] Example 10

[0059] The difference between this embodiment and embodiment 1 is that the acupuncture density is 50 punctures / cm 2 The needle puncture depth is 10 mm and the water puncture pressure is 250 bar.

[0060] Embodiment 11

[0061] The difference between this embodiment and embodiment 1 is that the acupuncture density is 60 punctures / cm 2 The needle puncture depth is 11 mm and the water puncture pressure is 260 bar.

[0062] Example 12

[0063] The difference between this embodiment and embodiment 1 is that the acupuncture density is 100 punctures / cm 2 The needle puncture depth is 15 mm and the water puncture pressure is 360 bar.

[0064] Example 13

[0065] The difference between this embodiment and embodiment 1 is that the acupuncture density is 110 punctures / cm 2 The needle puncture depth is 16 mm and the water puncture pressure is 380 bar.

[0066] Embodiment 14

[0067] The only difference between this embodiment and embodiment 1 is that the impregnated filter material felt is squeezed with liquid at a pressure of 6.5 bar. After squeezing, the liquid content of the impregnated filter material felt is 78%. The felt is then dried in an oven for shaping at a temperature of 250°C and an oven speed of 6 m / min to obtain a stiff filter material felt.

[0068] Embodiment 15

[0069] The only difference between this embodiment and embodiment 1 is that the impregnated filter material felt is squeezed with liquid at a pressure of 7 bar. After squeezing, the liquid content of the impregnated filter material felt is 70%. It is then dried and shaped in an oven at a temperature of 240°C and an oven speed of 6 m / min to obtain a stiff filter material felt.

[0070] Example 16

[0071] The only difference between this embodiment and embodiment 1 is that the impregnated filter material felt is squeezed with liquid at a pressure of 8 bar. After squeezing, the liquid content of the impregnated filter material felt is 50%. It is then dried in an oven for shaping at a temperature of 140°C and an oven speed of 4 m / min to obtain a stiff filter material felt.

[0072] Embodiment 17

[0073] The only difference between this embodiment and embodiment 1 is that the impregnated filter material felt is squeezed with liquid at a pressure of 8.5 bar. After squeezing, the liquid content of the impregnated filter material felt is 41%. It is then dried in an oven for shaping at a temperature of 120°C and an oven speed of 4m / min to obtain a stiff filter material felt.

[0074] Embodiment 18

[0075] The only difference between this embodiment and embodiment 1 is that the polyester fiber is replaced by an equal amount of aramid fiber, and the polyester fabric is replaced by an aramid fabric containing conductive yarns in both the warp and weft directions of equal thickness.

[0076] Embodiment 19

[0077] The only difference between this embodiment and embodiment 1 is that the polyester fiber is replaced by an equal amount of PPS fiber, and the polyester fabric is replaced by a PPS fabric containing conductive yarns in both the warp and weft directions of equal thickness.

[0078] Comparative Example

[0079] Comparative Example 1

[0080] The only difference between this comparative example and Example 1 is that the stainless steel fiber is replaced by an equal amount of polyester fiber.

[0081] Comparative Example 2

[0082] The only difference between this comparative example and Example 1 is that the polyester fiber and the stainless steel fiber are mixed in a weight ratio of 100:4 to obtain the mixed fiber.

[0083] Comparative Example 3

[0084] The only difference between this comparative example and Example 1 is that the polyester fiber and the stainless steel fiber are mixed in a weight ratio of 100:11 to obtain the mixed fiber.

[0085] Comparative Example 4

[0086] The only difference between this comparative example and Example 1 is that no stainless steel mesh roll is installed inside the cylindrical filter material.

[0087] Comparative Example 5

[0088] The only difference between this comparative example and Example 1 is that no galvanized metal end caps are installed at both ends of the filter cartridge body, and the filter cartridge body is directly used as an antistatic folded filter cartridge.

[0089] Performance testing

[0090] The following performance tests were performed on the antistatic folded filter cartridges prepared in Examples 1-19 and Comparative Examples 1-5:

[0091] The weights of the filter material felt and stiff filter material felt in each embodiment and comparative example were weighed respectively, and the gram weight was calculated according to the following formula: gram weight = weight / area.

[0092] According to GB / T 12703.4-2010, the volume resistivity of stiff filter felt and the volume resistivity of antistatic pleated filter cartridge are tested.

[0093] According to GB / T12625-1990, the dust removal rate of the antistatic pleated filter cartridge is tested.

[0094] The test results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] Combining Example 1 and Comparative Examples 1-5 and Table 1, it can be seen that compared with Example 1, the volume resistance of the antistatic folded filter cartridges of Comparative Examples 1, 4 and 5 is significantly increased, the volume resistance of the stiff filter material felt of Comparative Examples 1 and 2 is significantly increased, and the volume resistance of the stiff filter material felt of Comparative Example 3 is reduced, but the dust removal rate of the antistatic folded filter cartridge of Comparative Example 3 is reduced. This shows that the volume resistance of the stiff filter material felt is reduced due to the addition of stainless steel fibers, and the volume resistance of the antistatic folded filter cartridge is reduced by using stainless steel mesh and galvanized metal end caps. However, adding too much stainless steel fiber may result in a decrease in the dust removal rate of the filter cartridge. Therefore, the raw material ratio and process conditions of Example 1 are used to help improve the antistatic properties of the stiff filter material felt and the antistatic folded filter cartridge, and to enable the stiff filter material felt and the antistatic folded filter cartridge to maintain a good dust removal rate.

[0099] It can be seen from Examples 1-5 and 18-19 and Table 1 that the stiff filter felt material and antistatic pleated filter cartridge of Examples 1-5 have a relatively small volume resistivity, and the dust removal rate of the antistatic pleated filter cartridge is greater than 99.99%. Therefore, the antistatic performance of the antistatic pleated filter cartridge can be improved by using the raw material ratio within the range of Examples 1-5.

[0100] Combining Examples 1, 6-9 and Table 1, it can be seen that the volume resistivity of the stiff filter felt materials of Examples 1, 6-9 is ranked from small to large as follows: Example 8 < Example 9 < Example 1 < Example 7 < Example 6, but the weight ratio of the conductive polyaniline microspheres in the antistatic agent is ranked from small to large as follows: Example 6 < Example 7 < Example 1 < Example 8 < Example 9. This indicates that within the range of the weight ratio of the potassium salt of fatty alcohol ether phosphate, the sodium salt of octadecylbenzenesulfonic acid and the conductive polyaniline microspheres being 1: (0.6-1.2): (0.3-0.6), the volume resistivity of the stiff filter felt material is smaller, which helps to further improve the antistatic performance of the antistatic folded filter cartridge.

[0101] Combining Examples 1, 10-13 and Table 1, it can be seen that as the needling density, needling depth and water puncture pressure increase, the weight of the filter material felt gradually increases. However, when the needling density is 60-100 punctures / cm 2 Under the process conditions of needling depth of 11-15mm and water spunlace pressure of 260-360bar, the volume resistance of the stiff filter felt material is smaller and the dust removal rate is high.

[0102] Combining Examples 1, 14-17 and Table 1, it can be seen that when the pressure of the squeeze liquid is less than 7 bar, the liquid carrying rate of the impregnated filter material felt is greater than 70%, and even if it is dried at a temperature higher than 240°C at the same speed, the stiffness of the filter material felt is still greater than 370g / m 2 When the pressure of the squeeze liquid is greater than 8 bar, the liquid carrying rate of the impregnated filter material felt is less than 50%. Even if it is dried at a temperature below 140°C at the same speed, the stiffness of the filter material felt is still less than 330g / m 2 , and the volume resistance of the stiff filter felt material increases significantly. This shows that when the liquid is squeezed out at a pressure of 7-8 bar, the liquid carrying rate of the impregnated filter felt is 50-70% after the liquid is squeezed out; the process condition of drying temperature of 140℃-240℃ is helpful to obtain a stiff filter felt material with small volume resistance and high dust removal rate.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an antistatic folded filter cartridge, characterized in that: The steps include: The synthetic fiber and the metal fiber are opened separately, and mixed in a weight ratio of 100:(5-10) of the synthetic fiber:the metal fiber to obtain a mixed fiber, and the cloth containing the conductive yarn is used as the base fabric, and the mixed fiber is combed, laid, combined and pre-needled to obtain a pre-needled felt; The pre-needled felt is subjected to hydroentanglement reinforcement to obtain a filter material felt; After the surface of the filter material felt is singed, it is immersed in a finishing agent, and the impregnated filter material felt is squeezed and dried to obtain a stiff filter material felt; After trimming and folding the stiff filter material felt, a fixing band is welded on the outer side of the stiff filter material felt, and the center seam of the stiff filter material felt is welded to obtain a cylindrical filter material; A metal mesh roll is installed inside the cylindrical filter material, and the sealing of the fixing band is welded to obtain the main body of the filter cartridge; Galvanized metal end caps are installed at both ends of the main part of the filter cartridge to obtain an antistatic pleated filter cartridge.

2. The method for preparing an antistatic folded filter cartridge according to claim 1, characterized in that: The finishing agent comprises the following raw materials in weight percentage: 20-30% stiffening agent, 3-5% antistatic agent, 10-15% PTFE emulsion, 1-3% coupling agent, and the balance is water.

3. The method for preparing an antistatic folded filter cartridge according to claim 2, characterized in that: The antistatic agent comprises potassium salt of fatty alcohol ether phosphate, sodium salt of octadecylbenzenesulfonic acid and conductive polyaniline microspheres in a weight ratio of 1:(0.6-1.2):(0.3-0.6).

4. The method for preparing an antistatic folded filter cartridge according to claim 1, characterized in that: The weight of the stiff filter felt material is 330-370g / m 2 .

5. The method for preparing an antistatic folded filter cartridge according to claim 4, characterized in that: The weight of the filter material felt is 285-315g / m 2 .

6. The method for preparing an antistatic folded filter cartridge according to claim 5, characterized in that: When the impregnated filter material felt is squeezed and dried, the squeeze is carried out at a pressure of 7-8 bar. After the squeeze is completed, the liquid carrying rate of the impregnated filter material felt is 50-70%; The drying temperature is 140℃-240℃.

7. The method for preparing an antistatic folded filter cartridge according to claim 1, characterized in that: The density of pre-acupuncture is 60-100 punctures / cm 2 The needle puncture depth is 11-15mm, and the water puncture pressure of water puncture reinforcement is 260-360bar.

8. The method for preparing an antistatic folded filter cartridge according to claim 1, characterized in that: The synthetic fiber includes at least one of polyester fiber, aramid fiber or PPS fiber, and the cloth containing conductive yarn is any one of polyester cloth, aramid cloth or PPS cloth containing conductive yarn in both warp and weft directions.

Citation Information

Patent Citations

  • Dust removal filter bag

    CN109435375A

  • Anti-static filter material and preparation method thereof

    CN105498362A

  • Preparation method of flame-retardant and anti-static fabric for coal mines

    CN109763237A

  • Method for eliminating static electricity of wool knitted fabric

    CN110699837A

  • PPS fiber filter material with gradually changed density, preparation process and filter bag

    CN112191026A